Analisis dan Inovasi dalam Marketing Pembiayaan Pada Produk Griya Hasanah BSI KCP Pekanbaru Arifin Ahmad - Damayanti, Niken; Jamilah, Putri (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The growth of the financing sector in Indonesia has shown a significant increase, driven by the community's need for financial access for productive consumption and investment. Bank Syariah Indonesia (BSI) through its Griya Hasanah product seeks to meet the need for home ownership with sharia principles. This study uses a qualitative descriptive case study approach, with data obtained from observations and interviews at BSI KCP Pekanbaru Arifin Ahmad. The results of the study indicate that digitalization and changes in consumer behavior affect customer expectations for fast, transparent, and flexible financing services. BSI faces challenges from fintech and digital banks that offer innovative services and competitive costs. Therefore, a more personalized and effective digital-based marketing strategy is needed, as well as the use of big data and artificial intelligence to improve customer experience. In addition, analysis and innovation in the Griya Hasanah product must consider sharia principles and market needs. Recommendations for BSI include the development of a profit and loss sharing financing model to increase competitiveness and provide added value to customers. This study provides insight into the dynamics and challenges in developing sharia financing products in the digital era.